A literature review on delayed ettringite formation: mechanism, affect factors and suppressing methods. Issue 7 (4th April 2021) - Zhang, Yulu; Pan, Yifan; Zhang, Dakang
Abstract : The expansion deterioration that occurs in concrete structures exposed to high temperature fluctuation in wet environments is often attributed to delayed ettringite formation (DEF). Due to the complex mechanism and various factors that influence DEF, it is difficult to establish effective methods for predicting the expansion and suppressing deterioration. With the aim of improving the durability and long-term maintenance of concrete structures at risk of DEF expansion, this review paper summarises the required conditions and factors influencing DEF and provides a detailed description of the DEF mechanism. Previously proposed methods for suppressing DEF expansion are summarised in detail and their practical applicability is discussed. Furthermore, a review of literature regarding methods for predicting expansion development is provided, considering prevention of DEF expansion. This work clearly highlights the current status of DEF research, and the data summarised in this paper are expected to be a valuable reference for investigating control or suppression of DEF expansion.